Operationalization of One Health Approach in India: Still Miles to Go? - Deepak Saxena; Sandul Yasobant; Pachillu Kalpana; Zahiruddin Quazi Sayed; Pankaj Bhardwaj (Indian Journal of Community Medicine)
One health (OH) has been a buzzword in the political and academic fraternity during the last couple of years in India and globally. While OH is an integrated, unifying approach that aims to sustainably balance and optimize the health of people, animals and ecosystems, it recognizes the health of humans, domestic and wild animals, plants, and the wider environment (including ecosystems) are closely linked and interdependent. OH approach mobilizes multiple sectors, disciplines, and communities at varying levels of society to work together to foster well-being and tackle threats to health and ecosystems while addressing the collective need for clean water, energy, and air, safe and nutritious food, taking action on climate change, and contributing to sustainable development. Here, a comprehensive roadmap for operationalizing the One Health approach in India is proposed as the way forward.